The Influence of Supplemental Dietary Linoleic Acid on Skeletal Muscle Contractile Function in a Rodent Model of Barth Syndrome - Elkes, Mario; Andonovski, Martin; Vidal, Daislyn; Farago, Madison; Modafferi, Ryan; Claypool, Steven M.; LeBlanc, Paul J. (Frontiers in Physiology, 2021)
Barth syndrome is a rare and incurable X-linked (male-specific) genetic disease that affects the protein tafazzin (Taz). Taz is an important enzyme responsible for synthesizing biologically relevant cardiolipin (for heart and skeletal muscle, cardiolipin rich in linoleic acid), a critical phospholipid of mitochondrial form and function. Mutations to Taz cause dysfunctional mitochondria, resulting in exercise intolerance due to skeletal muscle weakness. To date, there has been limited research on improving skeletal muscle function, with interventions focused on endurance and resistance exercise. Previous cell culture research has shown therapeutic potential for the addition of exogenous linoleic acid in improving Taz-deficient mitochondrial function but has not been examined in vivo. The purpose of this study was to examine the influence of supplemental dietary linoleic acid on skeletal muscle function in a rodent model of Barth syndrome, the inducible Taz knockdown (TazKD) mouse. One of the main findings was that TazKD soleus demonstrated an impaired contractile phenotype (slower force development and rates of relaxation) in vitro compared to their WT littermates. Interestingly, this impaired contractile phenotype seen in vitro did not translate to altered muscle function in vivo at the whole-body level. Also, supplemental linoleic acid attenuated, to some degree, in vitro impaired contractile phenotype in TazKD soleus, and these findings appear to be partially mediated by improvements in cardiolipin content and resulting mitochondrial supercomplex formation. Future research will further examine alternative mechanisms of dietary supplemental LA on improving skeletal muscle contractile dysfunction in Taz knockdown mice.